Portelmis guianensis sp. nov. from French Guiana (Coleoptera: Elmidae) - Przewoźny, Marek; Fernandes, André S. (Zootaxa, 2012)
Portelmis guianensis sp. nov. is a new member of the Portelmis gurneyi–group. It was collected in Sinnamary, northern French Guiana. The species is externally similar to the other members of the genus, but males deviate considerably by the shape of the aedeagus. A detailed description and figures are given to facilitate easy identification of the new species. In addition, we have modified the key to species for males of the P. gurneyi–group given in Fernandes et al. (2010) by including the new species. The genus Portelmis Sanderson, 1935 now contains 5 members.